Rotational Dynamics of Proteins from Spin Relaxation Times and Molecular Dynamics Simulations - Ollila, O H Samuli; Heikkinen, Harri A; Iwaï, Hideo (The journal of physical chemistry. B, 2018)
Conformational fluctuations and rotational tumbling of proteins can be experimentally accessed with nuclear spin relaxation experiments. However, interpretation of molecular dynamics from the experimental data is often complicated, especially for molecules with anisotropic shape. Here, we apply classical molecular dynamics simulations to interpret the conformational fluctuations and rotational tumbling of proteins with arbitrarily anisotropic shape. The direct calculation of spin relaxation times from simulation data did not reproduce the experimental data. This was successfully corrected by scaling the overall rotational diffusion coefficients around the protein inertia axes with a constant factor. The achieved good agreement with experiments allowed the interpretation of the internal and overall dynamics of proteins with significantly anisotropic shape. The overall rotational diffusion was found to be Brownian, having only a short subdiffusive region below 0.12 ns. The presented methodology can be applied to interpret rotational dynamics and conformation fluctuations of proteins with arbitrary anisotropic shape. However, a water model with more realistic dynamical properties is probably required for intrinsically disordered proteins.
Keywords: izotopy dusíku; Bacterial Proteins; Nitrogen Isotopes; Intrinsically Disordered Proteins; Membrane Proteins; simulace molekulární dynamiky; membránové proteiny; Water; vnitřně neuspořádané proteiny; spinové značení; Helicobacter pylori; Spin Labels; proteinové domény; Molecular Dynamics Simulation; voda; bakteriální proteiny; Protein Domains